2020
DOI: 10.1093/heapro/daaa136
|View full text |Cite
|
Sign up to set email alerts
|

Communication strategies and media discourses in the age of COVID-19: an urgent need for action

Abstract: Summary Identified in December 2019 in China, the coronavirus 2019 (COVID-19) has been declared a Public Health Emergency of International Concern (PHEIC). Pandemics share features that increase fear. While some fear can stimulate preventive health behaviors, extreme fear can lead to adverse psychological and behavioral response. The media play a major role shaping these responses. When dealing with a PHEIC, the authorities’ communication strategies are embedded in a multilevel governance and a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 58 publications
0
39
0
1
Order By: Relevance
“…The study was conducted in accordance with the Declaration of Helsinki, was reviewed and approved by the Research Ethics Board of the CIUSSS de l'Estrie-CHUS (HEC ref: 2020-3674). Further details concerning the goals, objectives and methods of this broad research project can be found elsewhere [17,22]. The second phase of the international survey was conducted from 6-18 November 2020, following the pilot phase conducted in Canada only in April 2020 (n = 600) and the first international phase conducted in June 2020 (n = 8806).…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted in accordance with the Declaration of Helsinki, was reviewed and approved by the Research Ethics Board of the CIUSSS de l'Estrie-CHUS (HEC ref: 2020-3674). Further details concerning the goals, objectives and methods of this broad research project can be found elsewhere [17,22]. The second phase of the international survey was conducted from 6-18 November 2020, following the pilot phase conducted in Canada only in April 2020 (n = 600) and the first international phase conducted in June 2020 (n = 8806).…”
Section: Designmentioning
confidence: 99%
“…Various factors play important roles in coping with a highly stressful situation such as the COVID-19 pandemic and the ensuing turmoil [17]. Given that disruption, loss, and confusion due to the pandemic and the infodemic could realistically affect our everyday lives, recognizing and strengthening these protective factors might be key to mitigating the psychosocial impacts of the current crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Experiences of coherent structures have been linked to the ability to make compromises, participating in adapting and creating appropriate resources, and even develop trust in society and its institutions (Habermas, 2016;Kickbusch & Szabo, 2014;Marmot & Allen, 2013). Trust in the state and its governance emerged, in turn, as an important coping resource during the early stages of the Corona pandemic (Genereux et al, 2020;Généreux, David, O'Sullivan, et al, 2020;. Thus, providing populations with a coherent understanding of what is going on contributes to stabilising society.…”
Section: Politics and Policiesmentioning
confidence: 99%
“…Sharing experiences with your in-group can be a conscious-rising, empowering experience, which helps you to understand the structural components of your experience, and collectively seek solutions (Carr, 2003). The community emerges as an important coping resource in the face of disaster or conflict (Braun-Lewensohn et al, 2019;Braun-Lewensohn & Sagy, 2011;Braun-Lewensohn & Sagy, 2014;Généreux, David, O'Sullivan, et al, 2020;Généreux, Roy, O'Sullivan, & Maltais, 2020;Namihira, 2019). The community, and even national states, are crucial contexts for the experience of coherence in difficult times (Sagy et al, 2020;Sagy & Braun-Lewensohn, 2009;Sagy, 2015;Braun-Lewensohn et al, 2019;Ben David et al, 2017).…”
Section: Vertical Policy Coherence: From a Decision To Implementationmentioning
confidence: 99%
See 1 more Smart Citation